The Interpretation of Geological Verses in the Qur’an and Their Relationship with Modern Geological Theories - Muhammad Albadar Adren; Lukmanul Hakim; Ridwan Sholeh; M. Irwanda Saputra (Hikami : Jurnal Ilmu Alquran dan Tafsir, 2025)
This study discusses the relationship between the Qur’anic verses and modern geology through a scientific exegesis approach. The background of this research stems from the belief that the Qur’an not only contains moral and spiritual guidance but also reflects scientific principles that can be revealed through contextual interpretation. The main objective of this study is to explain the harmony between the Qur’an’s explanations of natural phenomena and modern geological theories such as the earth’s equilibrium, the formation of mountains, and the dynamics of the earth’s crust. The method used is a qualitative descriptive analysis of the interpretations of Hasbi Ash-Shiddieqy, Sayyid Quthb, and M. Quraish Shihab on three verses, namely QS. An-Nahl [16]:15, QS. Ar-Ra‘d [13]:3, and QS. Adz-Dzariyat [51]:47–48. The results of the study indicate that the concept of mountains as stabilizers of the earth, the continuous process of land formation, and the expansive motion of the universe reflect the compatibility between the revealed text and modern geological principles. In conclusion, the Qur’an implicitly contains scientific values that support the understanding of natural laws and reinforce the view that revelation and science complement each other. This research contributes to enriching scientific exegesis studies and encourages synergy between religious knowledge and modern science to build an integrative understanding of God’s creation.